Neutralization sensitivity of genital tract HIV-1: shift in selective milieu shapes the population available to transmit. (15th July 2021) - Kariuki, Samuel Mundia; Selhorst, Philippe; Abrahams, Melissa-Rose; Rebe, Kevin; Williamson, Carolyn; Dorfman, Jeffrey R.
Abstract : Objective: Previous studies indicate that transmitted/founder HIV-1 isolates are sensitive to neutralization by the transmitting donor's antibodies. This is true in at least a subset of sexual transmissions. We investigated whether this selection for neutralization-sensitive variants begins in the genital tract of the donor, prior to transmission. Design: Laboratory study. Methods: HIV-1 viruses from semen and blood of two male donors living with HIV-1 were tested for neutralization sensitivity to contemporaneous autologous antibodies. Results: In one donor, semen-derived clones ( n = 10, geometric mean ID50 = 176) were 1.75-fold [95% confidence interval (CI) 1.11–2.76, P = 0.018] more sensitive than blood-derived clones ( n = 12, geometric mean ID50 = 111) to the individual's own contemporaneous neutralizing antibodies. Enhanced overall neutralization sensitivity of the semen-derived clones could not explain the difference because these semen-derived isolates showed a trend of being less sensitive to neutralization by a pool of heterologous clade-matched sera. This relative sensitivity of semen-derived clones was not observed in a second donor who did not exhibit obvious independent HIV-1 replication in the genital tract. A Bayesian analysis suggested that the set of semen sequences that we analysed originated from a blood sequence. Conclusion: In some instances, selection for neutralization-sensitive variants during HIV-1 transmission begins in the genital tract of the donor and this may be driven by independent HIV-1 replication in this compartment. Thus, a shift in the selective milieu in the male genital tract allows outgrowth of neutralization-sensitive HIV-1 variants, shaping the population of isolates available for transmission to a new host.